Adverse Childhood Experiences Among Sexual Offenders: Associations With Sexual Recidivism Risk and Psychopathology. (October 2021) - Kahn, Rachel E.; Jackson, Krystine; Keiser, Kerry; Ambroziak, Gina; Levenson, Jill S.
Adverse childhood experiences (ACEs) are increasingly recognized as a public health crisis. Cumulative effects of these experiences lead to a wide range of deleterious physical and psychological outcomes. Prior research has identified higher prevalence rates of ACEs and increased criminal behavior in samples of individuals who have committed sexual offenses. In a sample of civilly committed individuals who have committed sexual offenses ( N = 317), we examined the prevalence of ACEs (cumulative scores and the two components of child harm and family dysfunction) and their association with risk for sexual recidivism and adult psychopathology. ACEs were much more prevalent in this sample compared with the general population and to lower risk samples of individuals who had committed sexual offenses. Although ACE scores were unrelated to risk for sexual recidivism, higher ACE scores were associated with increased risk of psychopathology, including anxiety disorders, depressive disorders, substance use disorders, and Antisocial Personality Disorder. ACEs related to family dysfunction were uniquely associated with Alcohol Use Disorder and the presence of a dual diagnosis of a paraphilia and personality disorder. Results suggest that higher risk individuals who commit sexual offenses may have greater need for trauma-informed models of care that recognize the effect of these experiences on their mental health and offense-related behavior.